2020
DOI: 10.3390/molecules25122771
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carbofuran Degradation Using Immobilized and Free Cells of Enterobacter sp. Isolated from Soil

Abstract: Extensive use of carbofuran insecticide harms the environment and human health. Carbofuran is an endocrine disruptor and has the highest acute toxicity to humans than all groups of carbamate pesticides used. Carbofuran is highly mobile in soil and soluble in water with a lengthy half-life (50 days). Therefore, it has the potential to contaminate groundwater and nearby water bodies after rainfall events. A bacterial strain BRC05 was isolated from agricultural soil characterized and presumptively identified as E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…cloacae isolated in this study and reported elsewhere in other studies. Other workers have also recovered the different species of Enterobacter from various soil habitats and characterized them by 16S rRNA partial gene sequence analysis and other state-of-the-art tools. …”
Section: Resultsmentioning
confidence: 99%
“…cloacae isolated in this study and reported elsewhere in other studies. Other workers have also recovered the different species of Enterobacter from various soil habitats and characterized them by 16S rRNA partial gene sequence analysis and other state-of-the-art tools. …”
Section: Resultsmentioning
confidence: 99%
“…The wide application, accompanied by the high toxicity of carbofuran, provokes the search for an effective and affordable way to remove it from the environment [54][55][56]. Glyphosate is also the subject of increased interest in terms of accumulating data on the harmful effects it causes on human and animal health [57].…”
Section: Discussionmentioning
confidence: 99%
“…Up until this study was done, no detailed study has done previously to unveil the molecular interaction between copper nanoparticle and carbofuran. However, previous study by Mustapha et al show that copper can inhibit the degradation of carbofuran, which related to the effect of copper in inhibiting hydrolysis enzyme [ 69 , 70 , 71 ]. This effect might make the carbofuran present longer in the body and potentially cause more damage.…”
Section: Discussionmentioning
confidence: 99%